Fast-X on the Z: Rapid evolution of sex-linked genes in birds - Mank, Judith E.; Axelsson, Erik; Ellegren, Hans (Genome Research, 2007)
Theoretical work predicts natural selection to be more efficient in the fixation of beneficial mutations in X-linked genes than in autosomal genes. This “fast-X effect” should be evident by an increased ratio of nonsynonymous to synonymous substitutions (dN/dS) for sex-linked genes; however, recent studies have produced mixed support for this expectation. To make an independent test of the idea of fast-X evolution, we focused on birds, which have female heterogamety (males ZZ, females ZW), where analogous arguments would predict a fast-Z effect. We aligned 2.8 Mb of orthologous protein-coding sequence of zebra finch and chicken from 172 Z-linked and 4848 autosomal genes. Zebra finch data were in the form of EST sequences from brain cDNA libraries, while chicken genes were from the draft genome sequence. The dN/dS ratio was significantly higher for Z-linked (0.110) than for all autosomal genes (0.085; P = 0.002), as well as for genes linked to similarly sized autosomes 1–10 (0.0948; P = 0.04). This pattern of fast-Z was evident even after we accounted for the nonrandom distribution of male-biased genes. We also examined the nature of standing variation in the chicken protein-coding regions. The ratio of nonsynonymous to synonymous polymorphism (pN/pS) did not differ significantly between genes on the Z chromosome (0.104) and on the autosomes (0.0908). In conjunction, these results suggest that evolution proceeds more quickly on the Z chromosome, where hemizygous exposure of beneficial nondominant mutations increases the rate of fixation.
10.1101/gr.6031907